Exploration Ethnomathematics of the Malind Tribe for Character Building in Elementary Schools - Fredy Fredy; Yonarlianto Tembang; Gregorius Sebo Bito; Octarina Hidayatus Sholikhah (International Journal on Advanced Science, Education, and Religion, 2020)
This article aimed to explore ethnomathematics in the Malind tribe to strengthen the character values ​​of elementary school students. The method used descriptive survey method with data collection techniques such as observation, interviews, and literature review. The researchers act as a human instrument. The qualitative data were obtained and then analyzed by paying attention to ethnomathematics material or theme. The results showed: firstly, ethnomathematics in the culture of the Malind tribe was found in activities of daily life such as the manufacture of farming tools, hunting, fishing, musical instruments, noken, ornaments and paintings, traditional ceremonies, life behaviors, and traditional games. Second, the attitude of responsibility, like to work hard, practice religious values, develop creativity, friendship, responsibility, the spirit of cooperation and kinship and tolerance is an integrated national character in the cultural values ​​of the Malind tribe. Ethnomathematics can be integrated into learning mathematics in elementary schools Keywords: Ethnomathematics, Malind Tribe, Education Character